In vitro Effectiveness of Commercial Bacteriophage Cocktails on Diverse Extended-Spectrum Beta-Lactamase Producing Escherichia coli Strains - Gundogdu, Aycan; Bolkvadze, Darajen; Kilic, Huseyin (Frontiers in Microbiology, 2016)
The objective of this study is to determine the in vitro susceptibility of Georgian bacteriophage cocktails on multi-drug resistant extended-spectrum β-lactamase producing Escherichia coli (ESBL-EC) isolated from patients' blood and urine cultures. 615 E. coli isolates were included in this study. PhP-typing and phylogenetic grouping were used for the typing. Antimicrobial resistance profiles and ESBL production of all isolates were confirmed according to CLSI criteria. The activities of four bacteriophage cocktails (Enko-phage, SES-bacteriophage, Pyo-bacteriophage and Intesti-bacteriophage) were determined against 142 ESBL- EC using in vitro spot tests. According to this, Enko-phage were active against 87.3% of the tested strains while that ratio was 81.7% for intesti-bacteriophage, 81.7% for Pyo-bacteriophage and 59.2% for SES-bacteriophage cocktails. Based on the contingency tests, the phage cocktails were observed to be statistically significantly (p<0.001) more effective on ESBL-EC strains belonging to phylogenetic groups D and B2. The employed phage cocktails were found to be affective against all tested resistant types. These results are promising especially for the infections that are caused by multi-drug resistant pathogens that are difficult to treat. As this is a preliminary step to the potential clinical trials to be designed for the country, in vitro confirmation of their success on a multi-drug-resistant ESBL-EC collection should be accepted as an initial action, which is encouraging to consider clinical trials of phage therapy especially in countries which are not introduce phage therapy.